The Role Of Teachers In Influencing Character Values In The Digital Era In Students Of State Elementary School 2 Boal - Yuliana, Annisa; Ramlafatma, Ramlafatma; Zulkieflimansyah, Zulkieflimansyah (Jurnal Ilmiah Mandala Education (JIME), 2026)
The development of the digital era presents unique challenges in instilling character values in elementary school students. The role of teachers is crucial in guiding students to utilize technology wisely and foster positive character. This study aims to describe the role of teachers in instilling character values in the digital era among students at SD Negeri 2 Boal and identify supporting and inhibiting factors in its implementation.This study employed a qualitative approach with a descriptive design. Subjects included teachers, students, and parents selected purposively. Data collection techniques included observation, semi-structured interviews, and documentation. Data analysis employed the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing.The results of the study indicate that teachers have a strategic role in instilling character values through role models, habituation, integration of character values into the learning process, providing positive reinforcement, and utilizing digital media as an educational tool. The character values instilled include religiousness, nationalism, independence, cooperation, and integrity. Supporting factors for the implementation of character instillation include a positive school culture, habituation programs, the use of digital learning media, and parental support. Meanwhile, inhibiting factors include low parental supervision of gadget use, the negative influence of social media, limited digital resources, and differences in student backgrounds.This study concludes that teachers play a crucial role in instilling character values in the digital age. Character education will be more effective if implemented consistently and supported by strong collaboration between schools, parents, and the community.